Berseem seed and fodder production for Punjab’s dairy sector- A comparative economic analysis - Agnotra, Kajal; Kumar, Raj; Ranguwal, Sangeet (Indian Journal of Dairy Science, 2023)
The current study examines the on-farm profitability of berseem seed and fodder production in Indian Punjab from an innovative informal strategy for building a village-based forage seed enterprise for berseem (Trifolium alexandrinum). A comparative economic analysis of berseem seed, fodder, and wheat production in rabi season, 2019-20 found that berseem (as seed and fodder) was more profitable than wheat. Thus, there is a need to shift some area to berseem, particularly its seed production, which will not only help dairy producers increase their income but will also provide nutritious fodder for milch animals to reach their full potential. Quality seed production of improved varieties of berseem will also address the issue of recommended high-yielding varieties being unavailable during the peak sowing season. Berseem seed disposal patterns suggested that practically all seed produced by farmers was sold in the same year due to its high demand. Around 90% of growers reported that the primary challenge they faced during the production and marketing of berseem seed was high price volatility and losses during cleaning and grading, followed by an insufficient supply of high-quality seed (85%), a lack of an appropriate marketing channel (80%), and an inadequate price for the produce (80%). The primary challenge for berseem fodder growers was high labour costs (28%). Creating awareness among farmers/livestock keepers/policymakers about new berseem varieties, providing incentives, and ensuring a market for seed production will all contribute to increasing demand for quality fodder and, thus, seed production of berseem. The government should stabilize input and output prices, which can contribute significantly to sustaining higher productivity and the livelihoods of Punjab's dairy farmers, resulting in more effective rural development and poverty reduction.